(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic cerebral ischemia represents a progressive vascular condition characterized by insufficient blood supply to brain tissue, leading to cumulative neurological damage. This theoretical analysis examines the pathophysiological mechanisms underlying cognitive and emotional deterioration in patients experiencing prolonged cerebrovascular insufficiency. The study synthesizes current understanding of microangiopathic changes, neuroinflammatory processes, and functional network disruption that collectively compromise cognitive performance and emotional regulation. Findings demonstrate that fronto-subcortical circuit dysfunction and limbic system alterations constitute primary mechanisms for observed neuropsychiatric manifestations, with significant implications for early detection and therapeutic intervention strategies.